MiRNA-128-3p Restrains Malignant Melanoma Cell Malignancy by Targeting NTRK3 - Zhou, Xinxin; He, Jiayuan; Wang, Qingyuan; Ma, Teng (Frontiers in Oncology, 2021)
The functions of noncoding RNA, including microRNA (miRNA), have attracted considerable attention in the field of oncology, In this report, we examined the roles and molecular mechanisms of miR-128-3p, as related to the biological behaviors of malignant melanoma (MM). We found that miR-128-3p was expressed in low levels in these MM cells and may serve as a tumor suppressor by inhibiting proliferation, migration and invasion, as well as inducing apoptosis in these MM cells. Moreover, neurotrophin receptor 3 (NTRK3), which serves as an oncogene that can enhance malignant behaviors of MM cells, was up-regulated in MM cells. Our current survey disclosed a complementary binding between miR-128-3p and the NTRK3 3′ untranslated regions (3′-UTR), while luciferase activities of NTRK3 3′-UTR were restrained by miR-128-3p in 293T cells. The effects of pre-miR-128-3p and sh-NTRK3 as well as anti-miR-128-3p and NTRK3(+) appeared to function synergistically in producing malignant progression. Moreover, there were possible to have counteracted effects for pre-miR-128-3p and NTRK3(+) in malignant progression. These findings established that miR-128-3p can function as a tumor suppressor by inhibiting carcinogenesis of the oncogene, NTRK3. Collectively, miR-128-3p and NTRK3 genes participate in modulating the malignant behavior of MM, and may represent new therapeutic targets for MM.